SISTEM KLASTER DALAM PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) SIAP MENGAHADAPI TANTANGAN ASEAN FREE TRADE ASSOCIATION DAN MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Abdul Haris (Monex: Journal of Accounting Research, 2014)
The development of management theory developed very rapidly. early management pioneers was Robert Owen (1771-1858) and Charles Babbage (1792-1871), and continues to evolve with various schools and scientists in the field of view of the management of the flow of scientific management , classical to modern management. Therefore, the discussion and understanding of the management of the target, need to know first the development of theories and principles that will provide a " foundation " for a strong understanding of further developments. Cluster system approach in the development and empowerment of Micro, Small and Medium evoluasi included in management theory with the execution of change and innovation in management systems. Cluster system approach is assessed according to applied in the face of challenges to the adoption of the Asean Free Trade Association and the Asean Economic Community in 2015. Is Indonesia ready? Best answer is TO BE READY . Micro, Small and Medium Enterprises has advantages and important role in the Indonesian economy. Evident during the financial crisis of 1997-1998 at least affected compared to the corporate level. The role of the Government to continue to develop and empower the Micro, Small and Medium Enterprises is essential in order to compete in the era of globalization. Cluster system is an agglomeration economy, involving businesses from upstream to downstream, create collaboration, synergy, not the gap and social inequality, growing together to overcome some obstacles, particularly in the areas of production, marketing and capital.Key Word: Cluster, Micro Small and Medium Enterprises, the Asian Free Trade Association